Analisis Perubahan Morfologi Sungai Rokan Berbasis Sistem Imformasi Geografis Dan Penginderaan Jauh - Randa Kurniawan; Sigit Sutikno; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The river morphology is a geometry (shape and size), the type, property and circumstance of the river with all aspects and changes in the dimensions of space and time. Extreme changes in river morphology would be harmful to the assets in the region around the river. This study is located in downstream of Rokan river that was analyzed by using Geographical Information Systems and remote sensing. To investigate the rate and extent change, this study extract the river change from satellite data during 1988 to 2016. Changes would be reviewed is limited to changes horizontally divided into two classes of areas including erosion and deposition area. The data that used is imagery satellite data those are Landsat-5 TM, Landsat-7 ETM+, and Landsat-8 OLI_TIRS that were obtained from the USGS (United States Geological survey). Based on the analysis results, it was obtained that total morphological changes of Rokan river eroded area of 2799.63 ha with an erosion rate average of 101.69 ha / year and covering an area of 2541.95 ha deposited with a deposition rate average of 92.33 ha / years. The magnitude of the changes in river morphology of Rokan River has broken meanders neck, resulting in severance and change the direction of the river flow. Morphological changes of Rokan River that occurred also pose a potential breakup of a meander, damaging transport infrastructure, settlements and plantations eroded residents area around the Rokan River.Keywords: River morphology, geographic information systems, satellite imagery, erosion, deposition.